Sword and Shield of Zion : the Israel Air Force in the Arab-Israeli Conflict, 1948-2012. - Rodman, David (Sussex Academic Press, 2013)
The Israel Air Force (IAF) has accumulated as much battle experience as any air force in the world during the post-Second World War era, and it has recorded many outstanding accomplishments throughout a seemingly endless string of interstate wars, asymmetrical wars, counterinsurgency campaigns, and special operations.? This book examines the IAF's experience in the Arab?Israeli conflict from the establishment of Israel in 1948 to the present day. It analyzes this experience through the prisms of maneuver warfare, attrition warfare, counterinsurgency warfare, special operations, and humanitari.